A Comparative Study to Evaluate the Efficacy of Valacyclovir and Famcyclovir in the Management of Herpes Zoster in a TCH of KPK - Amjad Mustafa, Shabir Hussain, Ghafoor Ullah, Arif Mumtaz, Ghazala Shaheen, Fawad Qaiser (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: To evaluate the efficacy of valacyclovir and famcyclovir in the management of herpes zoster in a tertiary care hospital of Khyber Pakhtunkhwa. Design of the Study: It was a randomized controlled Trial. Study Settings: The study was conducted at Department of Pharmacology over 1 year from March 2020 to March 2021 at DHQ Teaching Hospital, Kohat. Material and Methods: Patients were divided into two groups to valacyclovir 1000mg thrice daily or Famciclovir 500mg thrice daily in a 1:1 ratio was given to patients for a period of seven days. Seven days after treatment began, patients underwent pain and healing of the cutaneous lesions evaluations, which continued for three weeks. On the 7th day of treatment, patients were given a Visual analogue scale to assess their level of pain. Results of the Study: In the famciclovir therapy group, the percentages of patients reporting mild, moderate, or severe pain were 0 percent, 63.9 percent, and 30.6 percent by the end of day seven. Valacyclovir therapy was associated with just 1%, 69%, and 12.33 % of patients reporting mild to moderate pain correspondingly. Conclusion: The result showed that both the interventions are effective and safe for treating acute herpes zoster. Famciclovir in comparison to valacyclovir demonstrated a significant advantage for the complete cessation of herpes zoster associated pain. Both the intervention had virtually equivalent efficacy in complete healing of herpes zoster